2007
DOI: 10.1007/s11695-007-9062-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation in Morbidly Obese Subjects: Response to Oral Supplementation with Alpha-Linolenic Acid

Abstract: 1) Various inflammatory markers were elevated in the studied population, although not necessarily exceeding the normal range; 2) Significant reduction could be demonstrated; 3) Some persistent effects of flaxseed supplement 2 weeks after discontinuation were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 25 publications
3
73
1
Order By: Relevance
“…In the current protocol, BMI exhibited virtually no correlation with biochemical, inflammatory or arterial variables, in disagreement with established experience in lesser forms of obesity [1,2,5,6].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In the current protocol, BMI exhibited virtually no correlation with biochemical, inflammatory or arterial variables, in disagreement with established experience in lesser forms of obesity [1,2,5,6].…”
Section: Discussioncontrasting
confidence: 93%
“…The classic atherogenic cluster of metabolic syndrome and its component feature of hyperglycemia, and particularly of hypertriglyceridemia which stood out on multivariate analysis, never switched sides and continued to move in parallel with vascular structural and physiologic deterioration. The same could be affirmed for older age, male gender and high blood pressure, on the basis of both uni-and multivariate tests (Tables 6 and 7) [5][6][7].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, we believe that it is important to know exactly the behavior of these inflammatory parameters in patients having a "normal" postoperative evolution, and this routine monitoring for inflammation could be useful in determining the presence of an abnormal response. We agree with the Sao Paulo group, when they propose that all these determinations could be useful in the bariatric surgeon's arsenal in order to detect any early infectious complications [18]. In short, the first 5 days after gastric bypass surgery, a significant increase in the white blood cell count and C-reactive protein is observed.…”
Section: Discussionsupporting
confidence: 74%
“…α-linolenic acid is an essential polyunsaturated fatty acid dependent on foods ingestion that contain it, since it cannot be synthesized by the human body. From 41% of the total fat present in flaxseed oil, 57% come from the omega 3, which has anti-inflammatory, anti-thrombotic, and anti-arrhythmic properties 8 . Based on the results of clinical trials, epidemiological investigations, and experimental studies, it has been suggested that ALA intake has a high impact on cardiovascular disease (CVD), For this reason, the use of flaxseed has been advocated in the prevention of heart disease and therefore the MS, which is currently the most common metabolic disease among these patients 9 .…”
Section: Introductionmentioning
confidence: 99%